2010
DOI: 10.1038/onc.2010.242
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL treatment provokes mutations in surviving cells

Abstract: Chemotherapy and radiotherapy commonly damage DNA and trigger p53-dependent apoptosis through intrinsic apoptotic pathways. Two unfortunate consequences of this mechanism are resistance due to blockade of p53 or intrinsic apoptosis pathways, and mutagenesis of non-malignant surviving cells which can impair cellular function or provoke second malignancies. Death ligand-based drugs, such as tumor necrosis factor-related apoptosis inducing ligand (TRAIL), stimulate extrinsic apoptotic signaling, and may overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 50 publications
3
67
1
Order By: Relevance
“…Supporting an oncogenic role for failed apoptosis following TRAIL-treatment, another study found that sub-lethal doses of TRAIL (and FAS ligand) led to caspase-dependent mutations and genomic instability in surviving cells 72 .…”
Section: Failed Apoptosis and Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…Supporting an oncogenic role for failed apoptosis following TRAIL-treatment, another study found that sub-lethal doses of TRAIL (and FAS ligand) led to caspase-dependent mutations and genomic instability in surviving cells 72 .…”
Section: Failed Apoptosis and Cancermentioning
confidence: 99%
“…Recent data show that cells which initiate apoptosis but do not die -we term this failed-apoptosis-sustain potentially oncogenic damage such as genomic instability and gene amplification (Figure 3) [71][72][73] . The failure to commit suicide is puzzling given what we know about apoptosis.…”
Section: Failed Apoptosis and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the role in migration, another mission of caspase-8 has been unveiled. Exposing of sublethal doses of TRAIL, which is used to overcome resistance in intrinsic apoptotic pathways, caused DNA breaks in glioma and mouse embryonic fibroblasts (Lovric and Hawkins, 2010). It has been observed that these mutations occur through the activation of caspase-activated DNase (CAD), which is inhibited by active caspase-8 substrate, the inhibitor of CAD.…”
Section: Caspases In Tumor Cell Repopulation and Motilitymentioning
confidence: 99%